Competitive Authoritarianism in the Era of Cohabitation: Neopatrimonialism and Transhumance in the Democratic Republic of the Congo - Buhendwa, Martin Mema (Université d'Ottawa | University of Ottawa, 2025)
Although there is abundant literature on cohabitation and the peaceful exit of autocrats from power, rarely have scholars studied the two events occurring simultaneously in a singular state. My goal was to fill this knowledge gap and to provoke new thoughts around cohabitation as an emerging practice of authoritarian resilience. Scholars have extensively theorized that authoritarian rulers are mainly driven by the desire to preserve power (Bueno de Mesquita et al., 2003), prompting academics to explore the different strategies autocrats use to sustain their survival (Levitsky and Way, 2010). While some scholars have projected the political “death” of autocrats after losing power, others have focused on studying what happens to the regime when the autocrat begins to age (Tanaka, 2018). Thus, this study aimed to build on the literatures that emphasize the political ‘death’ of autocrats after ceding power by investigating the political “afterlife” of an autocrat in his post-tenure period. In the last two decades, there has been a growing scholarly interest in studying how autocrats prepare to exit from power and how their post-tenure exit strategies influence whether they will leave office peacefully or face a severe ending. Building on Englebert’s (2019) study, I investigate how a former autocrat, despite not having an official position, ensured that the opposition remained loyal to the deal it made – a “devil’s bargain,” where the new president would ascend to power while the former ruler controlled the legislative majority (Englebert, 2020). My second aim was to examine how the new ruler, who rose to power without the legislative majority, managed to gradually dismantle his predecessor’s control over the state’s institutions and shift the balance of power to his favor during the cohabitation period. As a qualitative research design based on an interpretative case study, the key objective of my dissertation was to trace the residual shadow of the former ruler, Joseph Kabila, and Felix Tshisekedi’s trajectory of power consolidation.
Keywords: Competitive Authoritarianism; Cohabitation; Neopatrimonialism; Power Struggle; Political elites; Transhumance; Democratic Republic of the Congo